(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
permanent magnet synchronous machines (motors) (PMSM) are getting increasingly involved in electrical engineering and electric power sector. The possible application for PMSM is autonomous decentralized low-power source which requires electric starter-generator.Structure designing electric starter-generator for the autonomous cogeneration plant based on the rotary-vane external combustion vehicle (RVECE) is mostly consists of designing electric energy generating system. But the designing and investigating system starting operating modes is also of interest.The paper considers structures of the starter-generator for autonomous low-power sources based on RVECE, the test stand composition and the experiment results.